Genetic dysregulation in recurrent respiratory papillomatosis. (11th March 2014) - Rodman, Regina; Mutasa, Simukayi; Dupuis, Crystal; Spratt, Heidi; Underbrink, Michael
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Recurrent respiratory papillomatosis (RRP) is a devastating disease, caused by infection of the upper aerodigestive tract with human papillomavirus types 6 and 11. There is no cure for RRP, and surgical removal is the mainstay of treatment. The purpose of this project was to compare genes of cell cycle, apoptosis, and inflammatory cytokines in laryngeal papilloma versus normal tissue for a better understanding of the molecular mechanisms of the disease to discover novel therapies. Study Design Basic science research study. Methods Papilloma tissue was obtained from patients requiring surgical debridement. For comparison, normal mucosa was obtained from the excised uvula of patients undergoing uvulopalatopharyngoplasty. Total RNA was extracted from both groups and then probed using customized reverse transcriptase real time polymerase chain reaction gene arrays. Results The custom arrays examine expression of 84 separate genes within the cell cycle, apoptosis, and inflammatory cytokine pathways. Our findings based on 11 papilloma samples run in comparison to normal mucosa shows that the MCL−1 gene of the apoptosis pathway is significantly downregulated. cytokine genes IL1‐A, IL‐8, IL‐18, and IL‐31 are also significantly dysregulated. Conclusions Genes of cell cycle and apoptosis are generally upregulated and downregulated, respectively, as expected in papilloma tissue, with MCL‐1 achieving significance when compared to normal tissue. The finding of particular interest is that inflammatory cytokine genes were significantly downregulated, including IL1‐A, IL‐18, and IL‐31. This finding may explain why patients infected with the virus are unable to mediate a T‐cell immune clearance of their disease. Level of Evidence NA Laryngoscope, 124:E320–E325, 2014